The Impact of Project-Based Learning (PjBL) Model on Secondary Students’ Creative Thinking Skills - Biazus, Marivane de Oliveira; Mahtari, Saiyidah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
This study aims to identify the impact of using the project-based learning (PjBL) model compared to the direct instruction learning model on secondary school students' creative thinking (CT) skills. Quasi-experimental with pretest-posttest control group design was carried out to achieve the research objectives. Fifty secondary school students randomly chosen as experimental group (n = 25) and control group (n = 25) participated in the study. Eight essay tests were used to collect students' CT based on fluency, flexibility, originality, and elaboration indicators. Data were analyzed descriptively (n-gain) and statistically using paired t-test and independent sample t-test. The result shows that students' CT significantly improved after learning for the experimental group (n-gain = 0.47; p < 0.05) and the control group (n-gain = 0.25; p < 0.05). However, students' CT in the experimental group was significantly different compared to the control group achievement (p < 0.05). Thus, the conclusion proposed that the PjBL model significantly impacts secondary school students' CT skills on the temperature and expansion material.